EFFECT OF Mn-Ti IONS DOPING AND SINTERING TEMPERATURE ON PROPERTIES OF BARIUM HEXAFERRITE - Achmad Maulana Soehada; Kerista Sebayang; Toto Sudiro; Candra Kurniawan; Perdamean Sebayang (Jurnal Sains Materi Indonesia, 2014)
EFFECT OF Mn-Ti IONS DOPING AND SINTERING TEMPERATURE ON PROPERTIES OF BARIUM HEXAFERRITE. Mn-Ti doped (0, 0.1, 0.4, 0.5, and 0.6 mole%-barium hexaferrite powders have been prepared from BaCO3, Fe2O3, TiO2 andMnO powder by mechanical alloying technique for 20 hours. The mixture powder were grinded and then dried at 100 °C for 24 hours, followed by calcined at 1,000 °C for 2 hours. The calcined powder was then crushed into 400 mesh (38 μm) in particle size. X-Ray Diffraction analysis was performed to determine the phase formed. The powder was mixed with 3 wt%Celuna WE -518 polymer, and compressed with applied force of 5 tons. The sintering process was done at temperatures of 1100 °C and 1150 °C for 2 hours. The microstructure of sintered samples was observed by Scanning Electron Microscope - Energy Dispersive X-Ray Spectroscopy (SEM-EDS). The magnetic properties and Reflection Loss (RL) was measured by permeagraph Magnet-Physik and Vector Network Analyzer (VNA), respectively. The results show that the remanance (Br) of samples are likely to decrease with increase in %mol of Mn-Ti and the optimum coercivity (HCJ) 4,42 kOe was achieved at 0,5 mole% Mn-Ti. The maximum reflection loss of -25,6 dB was obtained at 0,4mole%Mn-Ti with sintering temperature of 1100 °C for 2 hours. Accordingly, it can be potentially used for microwave absorption application.